An Analysis of Students' Ability in Differentiating Contrast Adverbia Clauses (Concession and Opposition) at English Department of Universitas Negeri Padang - Yolla Suryani Putri; Fitrawati Fitrawati (Journal of English Language Teaching, 2020)
This study analyzes the student ability in differentiating contrast adverbial clause(Concession and opposition) at English department of Universitas Negeri Padang. This research is a descriptive qualitative research used in analysing the students ability in differentiating contrast adverbial clause. The instrumentation of this research was a test. From 915 items analysed, the research found that second-year students’ ability in differentiating contrast adverbial clause at English Department of UNP was adequate. It was also found that the mistakes done by the students in using conjunction were 31.26%. This finding indicated that the second-year students at English Department of UNP less understand about contrast adverbial clause.